Enhancement of dose response and nuclear magnetic resonance image of PAGAT polymer gel dosimeter by adding silver nanoparticles - Sabbaghizadeh, Rahim; Shamsudin, Roslinda; Deyhimihaghighi, Najmeh; Sedghi, Arman (Public Library of Science, 2017)
In the present study, the normoxic polyacrylamide gelatin and tetrakis hydroxy methyl phosphoniun chloride (PAGAT) polymer gel dosimeters were synthesized with and without the presence of silver (Ag) nanoparticles. The amount of Ag nanoparticles varied from 1 to 3 ml with concentration 3.14 g/l, thus forming two types of PAGAT polymer gel dosimeters before irradiating them with 6 to 25 Gy produced by 1.25-MeV 60Co gamma rays. In this range, the predominant gamma ray interaction with matter is by Compton scattering effect, as the photoelectric absorption effect diminishes. MRI was employed when evaluating the polymerization of the dosimeters and the gray scale of the MRI film was determined via an optical densitometer. Subsequent analyses of optical densities revealed that the extent of polymerization increased with the increase in the absorbed dose, while the increase of penetration depth within the dosimeters has a reverse effect. Moreover, a significant increase in the optical density-dose response (11.82%) was noted for dosimeters containing 2 ml Ag nanoparticles.